Effectiveness of Mediation in Resolving Business Disputes in the Digital Era - Krisdiyanto, Aris; Chai, Nong; Kiat, Ton (Rechtsnormen: Journal of Law, 2025)
Background: The digital era has transformed the landscape of business disputes, leading to a rise in conflicts arising from online transactions, e-commerce, and digital platforms. Traditional dispute resolution methods often struggle to address the unique challenges posed by these digital disputes, prompting a growing interest in alternative methods such as mediation. Objective: This study aims to evaluate the effectiveness of mediation in resolving business disputes within the digital environment. Specifically, it investigates how mediation compares to other traditional dispute resolution methods and its impact on time efficiency, cost, and overall satisfaction for businesses involved in digital disputes. Method: A mixed-method approach was used, combining quantitative surveys from businesses that have engaged in digital mediation with qualitative interviews of legal experts and mediators. The data were analyzed to assess key factors such as cost, time savings, and satisfaction in resolving disputes. Results: The findings indicate that mediation is significantly more cost-effective and time-efficient compared to litigation. Most participants expressed high satisfaction with the mediation process, noting its flexibility and ability to preserve business relationships. Conclusion: Mediation proves to be an effective method for resolving business disputes in the digital era, offering benefits in terms of cost, time, and relationship management. Businesses are encouraged to adopt mediation as a primary dispute resolution strategy.